Effect of SnS thin film thickness on visible light photo detection. (1st June 2022) - Alagarasan, Devarajan; Hegde, S S; Varadharajaperumal, S; Aadhavan, R; Naik, R; Shkir, Mohd; Algarni, H; Ganesan, R
Abstract: In this study, SnS thin films of various thicknesses (500 nm–700 nm) were prepared by the thermal evaporation technique for potential photodetector application. High purity SnS prepared at 1000 °C is used to deposit thin films at room temperature. The prepared SnS thin films were characterized to assess the thickness effect on the crystallite size, morphology, transmittance, band gap, and photo-sensing properties. SnS pure phase confirmed through XRD and Raman spectral analysis. Among the fabricated SnS thin films, the sample having a thickness of 650 nm showed better crystallinity with higher crystallite size and preferred orientation of crystallites. SnS grew plate-like-columnar grain morphology of different widths and thicknesses which is confirmed by FESEM results. The UV–Vis studies showed a minimum band gap value obtained for 650 nm thickness film. The 650 nm thickness SnS films have a highest photo response of 6.72 × 10 −1 AW −1, external quantum efficiency (EQE) of 157%, and detectivity of 14.2 × 10 9 Jones. The transient photo-response analysis showed the 650 nm SnS thin film has a 5.3 s rise and 5.1 s fall duration, which is better suitable for photodetector applications compared to other samples.